PENGARUH LITERASI KEUANGAN, TINGKAT PENDIDIKAN, DAN PENDAPATAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN INDUSTRI KECIL MENENGAH:Studi Kasus Pada Produsen Tempe di Kelurahan Semanan, Kecamatan Kalideres, Jakarta Barat - Kisti Paramita (2020)
The aim of this paper is to find out the effect of financial literacy, level of education, and income on financial management of small and medium sized business (sme) tempe producers in Semanan Village, Kalideres Sub-district, West Jakarta. This research is a quantitative research. This research is used small and medium sized business that produce tempe in semanan village, kalideres district as a population. The method used is probability sampling particularly simple random sampling with size samples of 92 respondents. Data collection was done by spread the questionnaire. Analysis techniques which used is Partial Least Square (PLS) analysis method. The research result show that financial literacy, level of education, and income has a significant impact on financial management behavior.